2009
DOI: 10.1080/09723757.2009.11886073
|View full text |Cite
|
Sign up to set email alerts
|

CD209Promoter Single Nucleotide Polymorphism -336A/G and the Risk of Susceptibility to Tuberculosis Disease in the Moroccan Population

Abstract: Tuberculosis (TB) remains a major cause of morbidity and mortality worldwide. Mycobacterium tuberculosis is the causal agent of this infection and its major receptor is CD209 which is expressed on human Dendritic Cells (DC). This interaction could influence bacterial persistence and immunity response. The aim of this study was to evaluate the functional polymorphism -336G/A SNP in TB susceptibility in the Moroccan population. We performed a case-control study within a cohort that included 122 pulmonary TB pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(31 reference statements)
0
2
1
Order By: Relevance
“…The frequency of SNP -336A/G in some African regions, such as in South Africa (40.3%) and Guinea-Bissau (49.9%), is considerably higher than the frequency found in this study (P < 0.05) (Barreiro et al, 2006;Olesen et al, 2007). However, in some northern African countries, such as Tunisia and Morocco, the frequency of this polymorphism is not statistically different from that of European countries (Ben-Ali et al, 2007;Sadki et al, 2009). Moreover, the frequency of allele -336G observed in this study was significantly higher than the frequency observed in Asian populations, such as those of eastern China (7.3%) (Zheng et al, 2011), northern Thailand (9.5%) (Wichukchinda et al, 2007), and different regions of Taiwan (Table 2).…”
Section: Discussioncontrasting
confidence: 50%
“…The frequency of SNP -336A/G in some African regions, such as in South Africa (40.3%) and Guinea-Bissau (49.9%), is considerably higher than the frequency found in this study (P < 0.05) (Barreiro et al, 2006;Olesen et al, 2007). However, in some northern African countries, such as Tunisia and Morocco, the frequency of this polymorphism is not statistically different from that of European countries (Ben-Ali et al, 2007;Sadki et al, 2009). Moreover, the frequency of allele -336G observed in this study was significantly higher than the frequency observed in Asian populations, such as those of eastern China (7.3%) (Zheng et al, 2011), northern Thailand (9.5%) (Wichukchinda et al, 2007), and different regions of Taiwan (Table 2).…”
Section: Discussioncontrasting
confidence: 50%
“…The CD209 gene, encoding DC-SIGN, might play a crucial role in the pathogenesis of TB. The association between CD209 gene polymorphisms and TB risk was first reported in a South African populations by Barreiro et al [6]; however, as discussed above, conflicting data regarding the role of CD209 in TB susceptibility and presentation have been reported [12][15], [19]. Against this backdrop, we performed a meta-analysis to clarify the relationship between CD209 polymorphisms and TB risk.…”
Section: Discussionmentioning
confidence: 85%
“…The most extensively investigated relevant polymorphisms were CD209 ‐336A/G and ‐871A/G. A case–control study conducted by Sadki and colleagues revealed no statistically significant association between ‐336A/G polymorphism and pulmonary TB (Sadki et al., ). This finding is in agreement with results reported in Tunisian, north‐western Colombian, West African and eastern Chinese populations (Ben‐Ali et al., ; Gómez et al., ; Olesen et al., ; Yi, Zhang, Mo, Zhen, & Zhao, ; Zheng et al., ).…”
Section: Candidate Genes and The Risk Of Developing Tbmentioning
confidence: 99%